S114. THE EFFICACY OF "URGENT CONSULTATION REQUEST"; PRELIMINARY ANALYSIS OF A REAL-WORLD APP (REMIDCARE) FOR EARLY PSYCHOSIS. (18th May 2020) - Bonet, Lucia; Arce, David; Blanquer, Ignacio; Llacer, Blanca; Julio, Sanjuan
Abstract: Background: Patients are clamming for more personalized and closer clinical attention (Bonet et al. 2018). To this end, we developed RemindCare app. The app conducts daily and weekly assessments and this information is used to prevent relapses, to improve the therapeutic alliance and it is automatically included at the electronic clinical record of the hospital. Moreover, patients can contact clinicians by an "Urgent Consultation Request" (UCR), which is answered by a phone call in a period of 24-48h. This app was introduced in clinical practice in October 2018. Since then, 81 patients met criteria for inclusion and 57/81 (71%) started using the app. The aim of this study is to analyze the efficacy of this UCR to determine if this function can improve the real-world treatment of patients with early psychosis. Methods: RemindCare app, is offered as an extra-service to the usual psychiatric care of patients in an Early Psychosis Program (EPP) at the Clinic Hospital of Valencia, Spain (Bonet et al. 2019). No remuneration is offered to any patient or clinician to use the app. Data of 57 patients diagnosed with a psychotic disorder was analyzed: the 26.3% (15/57) used the UCR (UCR group) and the 73.7% (42/57) did not (Non-UCR group). Mean age of the sample was 31.5 (SD=9.3), 56.1% were male, 87.7% caucasian and 82.5% were single. Mean years of illness was 3.5 (SD=2.8), CGI mean 4.1 (SD=0.9), GAF mean 60.5 (SD=12.3) and PANSS mean 56.6 (SD=12.2). Results: Mean of months using the app was 8.4 (SD=4.5), 38.6% (22/57) of patients used the app for more than a year (12–13 months) and mean of engagement was 84.3 (SD=18.9). No significant differences were found between UCR and Non-UCR group in terms of demographic and clinical characteristics. However, there was a difference between groups in terms of engagement to the app (χ2= 6.3, p=0.04). The 93.3% of the UCR group had a percentage of engagement to the app between 81–100% compared to the 66.7% in the Non-UCR group and the number of visits to the Urgent Care Units (UCU) was also higher in the UCR group (χ2= 4.4, p=0.03). Additionally, only the 13.3% (2/15) of patients used the UCR for a psychotic symptom′s aggravation, the 33.3% (3/15) used it to inform of anxiety symptoms and another 33.3% (3/15) to change the clinical appointment. Moreover, the 66.7% (4/6) of patients who attended to UCU had previously made an UCR and they went to the UCU before that period of 24-48h of clinical response ended. Finally, there were no differences in terms of hospital admissions (χ2= 1.1, p=0.3) and psychotic relapses (χ2= 0.08, p=0.8) between groups. However, patients who stopped using the app had more relapses than patients who continued using it (χ2= 15.3, p<0.000). Discussion: To our knowledge, this is the first e-Health intervention systematically introduced in clinical practice. Rates of acceptance and engagement are high (71%; 84.3%) and nearly 40% of the sample is using the app for more than a year. Mean of engagement with the app, was extremely high among patients who used the UCR (93.3%; engagement between 81–100%) and although this UCR service was the most required in our previous survey (Bonet et al. 2018), these preliminary results suggest ¡ that the use of this alarm is not related to psychotic relapse detection. However, patients who use RemindCare app had less relapses than the ones who discontinue its use, which highlights the efficacy of the app. This, along with the high engagement and the positive feedback received, suggests that an improvement in real-world treatment of patients with early psychosis may be found in upcoming analysis.